2007
DOI: 10.1002/jms.1226
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption/ionization determination of molecular weight distributions of polyaromatic carbonaceous compounds and their aggregates

Abstract: Molecular weight distributions (MWDs) of model polyaromatic hydrocarbons (PAHs) and complex asphaltene samples have been investigated in laser desorption/ionization mass spectrometry (LDI-MS)experiments. Special efforts are devoted to the characterization of aggregation effects during the desorption process. It is found that non-covalent clusters of the PAHs and asphaltenes form readily in the desorbing plume. Aggregation is favoured in the experiments performed on dense samples at high laser energy and under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
131
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(145 citation statements)
references
References 60 publications
(129 reference statements)
14
131
0
Order By: Relevance
“…Some matrix-assisted laser desorption results are consistent with all other mass spectral techniques (Miller et al 1998). Very recently, it has been conclusively established that LDI MS can give rise to gas-phase aggregation if (1) too high a laser power is used, (2) too high a surface concentration of asphaltenes is used (or not), and (3) if fast ion extraction is used (Hortal et al 2006;Martinez-Haya et al 2007a, b). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Some matrix-assisted laser desorption results are consistent with all other mass spectral techniques (Miller et al 1998). Very recently, it has been conclusively established that LDI MS can give rise to gas-phase aggregation if (1) too high a laser power is used, (2) too high a surface concentration of asphaltenes is used (or not), and (3) if fast ion extraction is used (Hortal et al 2006;Martinez-Haya et al 2007a, b). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous experimental methods have been utilised to measure the molecular weight distribution of heavy oil, from which the mean molecular weight can be deduced. However, pronounced controversy arose from these different techniques [124][125][126][127][128][129]. We measured the photoionisation mass spectra of four samples of heavy oil using IR LD/ VUV PIMS at the photon energy of 9.8 eV [58], and typical peaks of hydrocarbon in saturates were observed.…”
Section: Heavy Oilsmentioning
confidence: 99%
“…Another problem with laser desorption is the formation of ionized clusters of molecules when using too high laser fluences or thick sample layers. Hortal et al [15,16] and Martinez-Haya et al [17] showed that the LD-MS spectrum of an asphaltene depended on the concentration of species in the sample and on the laser fluence applied. The thickness of sample applied to the target plate was a factor in the formation of aggregates or clusters of molecules in the reactive gas plume formed by the laser shot; thin layers were less likely to form cluster ions than thick layers.…”
Section: Introductionmentioning
confidence: 99%